Effectiveness of water spinach (Ipomoea reptans Poir) in mitigating acetylcholinesterase inhibition caused by organophosphate and carbamate pesticide - Sirita, Jinda; Pintakam, Kanjana; Khamthan, Phatanit; Suanmuang, Maneerat; Rakitikul, Waleepan (Agriculture and Natural Resources, 2024)
Importance of the work: Organophosphate (OP) and carbamate (CB) pesticides pose health risks by inhibiting acetylcholinesterase (AChE). Evaluating water spinach (Ipomoea reptans Poir) as a remedy could provide a natural, accessible, and non-toxic remedy to counteract pesticide exposure. Objectives: To evaluate the effectiveness of water spinach in reducing AChE inhibition caused by OPs and CBs, and to assess its toxicity using a GT-Pesticide Residue Test Kit. Materials & Methods: Gas chromatography and mass spectroscopy (GC-MS) were used to analyze important chemical compounds. The quantity of water spinach to reduce inhibition of AChE by OP and CB pesticides was investigated using spectroscopic techniques. Results: The sample tube colors were clearer than the control (I0, I50 =control and B1, L1, T1 = branch, leaf and top, respectively, of I. reptans with pesticide in the ratio of 1:1 (2.5 g:2.5 g) and B2, L2, T2 = branch, leaf and top, respectively, of I. reptans without pesticide, except L1 (I50). Based on GC-MS, the water spinach contained alcohol functional groups, facilitating nucleophilic substitution reactions, which reduced AChE inhibition by OPs and CBs. Spectroscopic analysis showed differing efficiencies: I. reptans reduced OP inhibition (3 times hydrolysis) better than CB inhibition (2 times hydrolysis). I. reptans tea was non-toxic to human gingival fibroblast at concentrations of 0.0001–1 mg/mL. Main finding: Water spinach consists of important compounds that could reduce the inhibition of AChE caused by OPs and CBs, as well as reducing the inhibition of OPS to a greater degree than the inhibition of CBs.